Debating anarchism : a history of action, ideas and movements - Finn, Mike (Michael Thomas) (London, England : Zed Books, 2021)
"This timely book introduces readers to anarchism's relationship to broader history, offering not simply a history of anarchism in the modern period, but a critical introduction to debates on anarchist history. Attention thus far has been biased towards intellectual history and key thinkers such as Proudhon, Bakunin and Kropotkin, but these studies have neglected the social movements and spaces which have seen 'anarchy in action' and marginalised the role of women and voices beyond Europe and the United States. Debating Anarchism offers a different perspective, engaging with women's anarchist experiences and grounding recent historical work on anarchism in Africa and Asia. Interrogating anarchism as a concept, a movement and a social reality the author guides the reader through the origins of anarchism in the age of revolutions, assessing experiences of anarchy in Russia, Spain, India and beyond. Tracing the development of 'the beautiful idea' through the twentieth century, Finn explores anarchism in the Cold War world through to postmodernity and the twenty-first century. This volume situates anarchism in the broader historiographies of the modern world, offering a unique starting point for students of history, politics and philosophy seeking to understand the abiding power of 'the beautiful idea' - a society without government"--
Introduction: Everywhere and Nowhere - The Problem with Anarchist Historiography -- Part I: Anarchism in an Age of Revolutions, 1840-1939 -- 1. Anarchy is Order: The Origins of 'The Beautiful Idea', 1840-1872 -- 2. Words vs. Deeds: Anarchism and Syndicalism Before the First World War, 1872-1914 -- 3. European Anarchisms: Russia and Spain -- 4. Global Anarchisms: India, Japan and Beyond -- Part II: 'The seeds beneath the snow': Anarchism in the Age of the Superpowers -- 5. The Last Anarchists? Anarchism, Decolonisation, and Protest in the Cold War World, 1945-1989 -- Part III: Anarchist 'turns': Anarchism in the Age of Postmodernity -- Conclusion: Anarchism and History in a 'second anarchist moment'
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Anarchism -- History; Social movements -- History; Social & cultural history; Electronic books